Influence of mothers’ and frontline health workers’ knowledge, attitude, and practices on infant and young child feeding and child nutrition: a cross-sectional study in aspirational districts of Assam, India - Randhawa, Sonali; Choudhury, Manisha; Choudhary, Devika Gali; Ballala, Ramnath; Hegde, Shailendra; Barman, Priyanka; Dogra, Vishal (Frontiers in Nutrition, 2024)
The knowledge, attitude, and practices (KAP) of mothers and frontline health workers (FLWs) on optimal infant and young child feeding (IYCF), are essential to reduce undernutrition and associated morbidities among under-five children. The study assessed the KAP of mothers (of 0 to 60 months old children) and FLWs on recommended IYCF practices; the association of mother's KAP with their demographic characteristics and children's nutritional outcome, and the prevalence of stunting, wasting, and underweight among 0 to 60 months old children in five high focused districts of Assam. Data were collected from 389 mothers, 456 children, and 138 FLWs using standard method. Out of 389 mothers, 29% had good knowledge, attitude, and practices, whereas 42% scored average and 29% had poor KAP towards IYCF practices. The mean KAP score increased significantly with improvement in variables like community, language, education level, monthly income, living conditions, etc. (p < 0.01). Less than half of the children were stunted (40%), one-third had wasting (28%) and about 43% were underweight. The odds of children developing stunting was 2.05 (CI = 1.04 -4.02) times when the mother's KAP score was less than 40% compared to those who had more than 60%, and similar findings were reported for wasting and underweight. Out of 138 FLWs, 56% scored good KAP score, 30% average, and 14% poor.